2022
DOI: 10.1186/s12916-022-02430-0
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination deficiency (HRD) score in aggressive prostatic adenocarcinoma with or without intraductal carcinoma of the prostate (IDC-P)

Abstract: Background Intraductal carcinoma of the prostate (IDC-P) is a subtype of prostate cancer featured by poor prognosis. Previous studies suggested IDC-P could have a potentially unstable genome. Homologous recombination deficiency (HRD) score is a result-oriented method to describe the genomic instability status. This study investigates the association of HRD scores with IDC-P and other clinicopathological factors and the prognostic implication of HRD scores in an aggressive prostate cancer cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Moreover, HRD with BRCA2 deletions may lead to a pathogenic MYC variant, which is closely associated with the progression of localized or castration‐naïve PC to CRPC. 31 Delayed diagnosis and treatment of patients with PC‐carrying BRCA2 deletions can lead to the epithelial–mesenchymal transition, followed by rapid disease progression due to DNA damage and genomic instability. 26 These findings strongly suggest that even heterozygous BRCA2 deletions can cause HRD due to loss of function and may accelerate the progression of localized PC to BCR and eventually CRPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HRD with BRCA2 deletions may lead to a pathogenic MYC variant, which is closely associated with the progression of localized or castration‐naïve PC to CRPC. 31 Delayed diagnosis and treatment of patients with PC‐carrying BRCA2 deletions can lead to the epithelial–mesenchymal transition, followed by rapid disease progression due to DNA damage and genomic instability. 26 These findings strongly suggest that even heterozygous BRCA2 deletions can cause HRD due to loss of function and may accelerate the progression of localized PC to BCR and eventually CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that tumors with BRCA2 deletions display pathological characteristics similar to those of intraductal carcinoma 29 and neuroendocrine differentiated tumors, 30 which are both poor prognostic indicators. Moreover, HRD with BRCA2 deletions may lead to a pathogenic MYC variant, which is closely associated with the progression of localized or castration‐naïve PC to CRPC 31 . Delayed diagnosis and treatment of patients with PC‐carrying BRCA2 deletions can lead to the epithelial–mesenchymal transition, followed by rapid disease progression due to DNA damage and genomic instability 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IDC-P patients are more likely to carry the BRCA2 gene or BRCA-like molecular alterations. These molecular characteristic changes suggest that PARP inhibitors, represented by olaparib, are among the therapeutic options for improving the clinical prognosis of IDC-P positive patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patient-derived tumor xenografts (PDX) in three carriers of germline BRCA2 mutations found that PDX of BRCA2-mutant tumors had a significantly higher incidence of IDC-P compared to PDX established from sporadic prostate cancer (42% vs. 9%, p = 0.015). 78 Zhu et al 79 performed homologous recombination deficiency (HRD) score analysis in 123 prostate cancer patients with untreated high-risk M0 and de novo M1 disease, with and without IDC-P. The HRD score, which directly results from the loss of homologous recombinant repair (HRR) function (genomic scars), is a result-oriented method of expressing genomic instability.…”
Section: Dna Damage Repair Gene Mutationsmentioning
confidence: 99%